Proceedings of the 2009 ACM International Conference on Supporting Group Work 2009
DOI: 10.1145/1531674.1531718
|View full text |Cite
|
Sign up to set email alerts
|

Locating patient expertise in everyday life

Abstract: Coping with a new health issue often requires individuals to acquire knowledge and skills to manage personal health. Many patients turn to one another for experiential expertise outside the formal bounds of the health-care system. Internet-based social software can facilitate expertise sharing among patients, but provides only limited ways for users to locate sources of patient expertise. Although much prior research has investigated expertise location and systems to augment expertise sharing in workplace orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…Demonstrating how sharing health information with others can benefit the patient will be important for showing the full value of such tools to patients. Previous work has examined how peer support can be enhanced in cancer care [4,20]. There remains an open opportunity for tools to allow new patients to learn from the experiences of doctors, navigators, and other patients.…”
Section: Support Sharing Of Past Experiencesmentioning
confidence: 99%
“…Demonstrating how sharing health information with others can benefit the patient will be important for showing the full value of such tools to patients. Previous work has examined how peer support can be enhanced in cancer care [4,20]. There remains an open opportunity for tools to allow new patients to learn from the experiences of doctors, navigators, and other patients.…”
Section: Support Sharing Of Past Experiencesmentioning
confidence: 99%
“…However, there has been relatively little work on exploring the ways in which people identify expertise relevant to their needs. Exceptions to this include [6,7] which highlighted the strategies that women with breast cancer take when trying to identify 'everyday' experts. We expand this work but deal with a context where there is no established common ground between individuals whose needs (and their understanding of these needs) are in flux and where access to local ALT resources is of greater concern than social support.…”
Section: Collaborative and Peer-to-peer Healthcarementioning
confidence: 99%
“…Civan et al [4] focused on how people 'source' or find health information expertise (e.g., finding disease information, a registered nurse, or someone who has previously had the disease). Their study found that people are careful not to burden family or friends with their health issues and only identify select individuals (gatekeepers) in their social network whom they rely on to help with expertise sourcing.…”
Section: Social Support For Patientsmentioning
confidence: 99%
“…Their study found that people are careful not to burden family or friends with their health issues and only identify select individuals (gatekeepers) in their social network whom they rely on to help with expertise sourcing. Civan et al defined three such gatekeeper roles: a conduit was responsible for funneling information to the patient and acting as a point of contact to pass messages from the patient to an external source; a contact broker would introduce participants to sources of expertise outside their support community; and, a champion was often a key source of expertise with a breadth of knowledge that crossed multiple domains (e.g., a registered nurse) [4]. Skeels et al [22] studied the ways in which family members support patients and found that two distinct roles exist: proxy and coordinator.…”
Section: Social Support For Patientsmentioning
confidence: 99%